India CSR report 2019 : trends and prospects of CSR - Srinivasan, Girija; Srinivasan, Narasimhan (Sage impact., 2019)
This report studies the evolution & historical background of Corporate Social Responsibility (CSR) and offers a comprehensive overview of the current CSR practices in India, it offers policy suggestions to improve effectiveness and enlarging the scope of CSR.